Efficacy of Metarhizium anisopliae and (E)–2–hexenal combination using autodissemination technology for the management of the adult greenhouse whitefly, Trialeurodes vaporariorum Westwood (Hemiptera: Aleyrodidae) - Paradza, Vongai M.; Khamis, Fathiya M.; Yusuf, Abdullahi A.; Subramanian, Sevgan; Akutse, Komivi S. (Frontiers in Insect Science, 2022)
The efficiency of an autodissemination technique in controlling adult whiteflies, Trialeurodes vaporariorum Westwood (Hemiptera: Aleyrodidae) on tomato, Solunum lycopersicum was investigated with previously identified potent fungal isolates of Metarhizium anisopliae ICIPE 18, ICIPE 62 and ICIPE 69 under semi–field conditions. The autodissemination device was inoculated with dry conidia of the M. anisopliae isolates, while control insects were exposed to a fungus–free device. Sampling for conidia uptake, conidial viability and persistence, and insect mortality was done at 1, 2, 3, 5 and 8 days post–exposure, and collected insects were monitored for mortality over ten days. Overall, mortality was higher in insects exposed to ICIPE 18 (62.8%) and ICIPE 69 (61.8%) than in those exposed to ICIPE 62 (42.6%), with median lethal times, (LT50) ranging between 6.73–8.54 days. The control group recorded the lowest mortality rates (18.9%). A general linear reduction in conidial viability with exposure time was observed, although this was more pronounced with M. anisopliae ICIPE 62. Insects exposed to M. anisopliae ICIPE 69 also recorded the highest conidia uptake, hence selected for further evaluation with a T. vaporariorum attractant volatile organic compound, (E)–2–hexenal. The volatile inhibited fungal germination in laboratory compatibility tests, therefore, spatial separation of M. anisopliae ICIPE 69 and (E)–2–hexenal in the autodissemination device was conducted. The inhibitory effects of the volatile were significantly reduced by spatial separation at a distance of 5 cm between the fungus and the volatile, which was found to be more suitable and chosen for the subsequent experiments. Results showed that (E)–2–hexenal did not influence conidia uptake by the insects, while fungal viability and the subsequent mortality variations were more related to exposure time. The fungus–volatile compatibility demonstrated with spatial separation provides a basis for the optimisation of the volatile formulation to achieve better T. vaporariorum suppression with an excellent autodissemination efficiency when used in the management of whiteflies under semi–field conditions.